Tracking cellular therapies to optimize homing against liver metastases - Purl, Megan C.; Shick, Alexandria; Canter, Robert J.; Judge, Sean J. (Frontiers in Immunology, 2025)
Novel cellular therapies have shown practice changing results in a range of hematologic malignancies, though success against solid tumors has been limited. Key factors limiting success of these therapies against solid tumors are homing to the site(s) of disease, engraftment, maintenance of function, and persistence. The inhospitable tumor microenvironment appears to provide barriers at every step of this process. The liver, a unique organ with diverse immunoregulatory functions, is a common site for metastatic disease from solid cancers of the gastrointestinal (GI) tract. Although the complex interplay between hepatocytes, circulatory and tissue resident immune cells, and the enterohepatic circulation has been investigated for some time, many unanswered questions about the immunobiology of the liver remain. More so, novel imaging techniques provide unparalleled insight into these interactions and shed light on these complex processes that can lead to an improved understanding of the tumor microenvironment in the liver and opportunities for improving homing of cellular therapy against liver tumors. In this review, we will provide a focused assessment of this burgeoning field and focus on the emerging tools for studying homing of these therapies and how they may be enhanced to better treat liver metastases.